2019
DOI: 10.1101/581223
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The autophagic response toStaphylococcus aureusprovides an intracellular niche in neutrophils

Abstract: Staphylococcus aureus is a major human pathogen causing multiple pathologies, from cutaneous lesions to life-threatening sepsis. Although neutrophils contribute to immunity against S. aureus, multiple lines of evidence suggest that these phagocytes can provide an intracellular niche for staphylococcal dissemination. However, the mechanism of neutrophil subversion by intracellular S. aureus remains unknown. Targeting of intracellular pathogens by autophagy is recognised as an important component of host innate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…For these experiments, the transgenic larvae Tg(fms: GFP)sh377 [34] were infected with D39ΔcpsGFP which were prestained with the pH-sensitive dye pHrodo Red [35], which creates a higher fluorescence intensity at lower pH. We found that bacteria internalised by macrophages were acidified in control larvae and this acidification was inhibited by bafilomycin A1 in the medium (Figures 4(a)-4(c)).…”
Section: Phagosomal Acidification Within Macrophages Ismentioning
confidence: 91%
“…For these experiments, the transgenic larvae Tg(fms: GFP)sh377 [34] were infected with D39ΔcpsGFP which were prestained with the pH-sensitive dye pHrodo Red [35], which creates a higher fluorescence intensity at lower pH. We found that bacteria internalised by macrophages were acidified in control larvae and this acidification was inhibited by bafilomycin A1 in the medium (Figures 4(a)-4(c)).…”
Section: Phagosomal Acidification Within Macrophages Ismentioning
confidence: 91%
“…Furthermore, association with LC3 is independent of ATG13, but is dependent on Rubicon and NADPH, which suggests that S. Typhimurium replication in macrophages is restricted by LC3-associated phagocytosis (LAP) [49]. For S. aureus infection, p62-mediated autophagy and LAP have opposing roles in neutrophils [50,51] because p62-selective autophagy promotes bacterial clearance, whereas LAP helps bacteria to establish an intracellular niche.…”
Section: Use Of Zebrafish To Discover Innovative Concepts In Host Defensementioning
confidence: 99%
“…However, some pathogens have evolved survival strategies in their favor, using autophagy for intracellular reproduction. This process has been achieved through LAP (Prajsnar et al, 2021). Therefore, we explored the exact mechanism of mutual recognition and induction of autophagy between pathogen and host cells, in which host cells can survive but bacteria cannot.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported on the relationship between the two and autophagy. Tomasz K. et al found that autophagy can provide an intracellular replication niche for S. aureus within neutrophils (Prajsnar et al, 2021). Meanwhile, Josie F. et al, in the same lab, found that the selective autophagy receptor Sqstm1/p62 in neutrophils could target and degrade S. aureus intracellularly (Gibson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation